A comparative analysis of objectively assessed physical activity levels in kindergarten and home among children aged 5 to 6 - Jarosław Herbert; Piotr Matłosz; Wojciech Ratkowski; Justyna Wyszyńska (PLoS ONE, 2026)
Children’s physical activity (PA) is positively associated with a wide range of developmental and health outcomes. This study compared individual levels of PA in children aged 5–6 years across two settings: kindergarten and home. A total of 522 children (51.9% girls) participated. PA was objectively measured using ActiGraph GT3X-BT accelerometers, and selected socioeconomic indicators (SSI) were parent-reported. Children accumulated significantly more light physical activity (PA) in kindergarten than at home, whereas moderate, vigorous, and total moderate-to-vigorous physical activity (MVPA) were significantly higher at home than in kindergarten (all p < 0.001). Boys showed consistently higher PA levels than girls in both environments. Notably, median MVPA in boys was 22.7 min at home and 17.3 min in kindergarten, compared to 19.0 and 14.0 min in girls, respectively. Median daily step counts in the total sample were also significantly higher at home (3315.5) than in kindergarten (3111.0). Significant associations were observed between selected SSI and PA. Lower parental education levels were associated with higher step counts, light (father’s education) and moderate PA (mother’s education) in kindergarten. Children from families with less favorable financial conditions also had higher MVPA in kindergarten. These findings underscore the importance of the home environment and suggest that certain aspects of socioeconomic disadvantage may be linked to higher PA levels in early childhood.